International libel and privacy handbook a global reference for journalists, publishers, webmasters, and lawyers - Glasser, Charles J. Jr (Bloomberg Press, 2009)
"A nation-by-nation summary of libel and privacy law, written by local practitioners in a reference format, covering Europe, Asia, and the Americas. Designed for rapid analysis of media law as it applies to globally accessible publications, this second edition includes new chapters on emerging media markets, as well as thorough legal updates on all major media nations"--Provided by publisher.